2014
DOI: 10.1007/978-3-319-10831-5_29
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Delay on Group Performance in Collaborative Editing

Abstract: Abstract. Real-time collaborative editing systems such as Google Drive are increasingly common. However, no prior work questioned the maximum acceptable delay for real-time collaboration or the efficacy of compensatory strategies. In this study we examine the performance consequences of simulated network delay on an artificial collaborative document editing task with a time constant and metrics for process and outcome suitable for experimental study. Results suggest that strategy influences task outcome at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Delays measured in GoogleDocs when the number of users exceeds ten are largely superior to the artificial delays experienced in [6], [12]. We therefore expect that a high hindrance of delay will be experienced in Google Docs in scenarios of collaborative editing that involve a large number of users that concurrently modify a shared document.…”
Section: Effect On Usersmentioning
confidence: 99%
See 2 more Smart Citations
“…Delays measured in GoogleDocs when the number of users exceeds ten are largely superior to the artificial delays experienced in [6], [12]. We therefore expect that a high hindrance of delay will be experienced in Google Docs in scenarios of collaborative editing that involve a large number of users that concurrently modify a shared document.…”
Section: Effect On Usersmentioning
confidence: 99%
“…The effect of delay on users' behavior in collaborative editing has been studied in [6], [12]. Twenty groups of four students from a French university have been recruited to perform an experiment including several tasks in collaborative editing.…”
Section: Effect On Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…The second task was analysed by Ignat et al (2014). The task that we present in this paper is the third task, on note taking.…”
Section: Methodsmentioning
confidence: 99%
“…They found that collaboration editing has grown rapidly up to 53% during the period they examined and 'concurrent editing is sticky' with 76% of the employees who participated in a 'concurrent session' repeating the activity in the following month. In [10,9] authors studied the effect of delay on the error rate, redundancy and quality of collaboratively produced documents by analyzing logs of real-time collaborative editing tasks using Etherpad. Olson et al [14] examined the traces of collaborative writing behavior of advanced undergraduates in a project course using Google Docs.…”
Section: Introductionmentioning
confidence: 99%